Influence of the Rancimat parameters on the determination of oxidative stability index of Sesamum Indicum L. Oil - Villanueva López, Eudes (2013)
The objective of this research was to determine the oxidative stability index (OSI) in virgin oil seed Sesamum indicum L. (Sesame) previously extracted by cold pressing, clarified by centrifugation and stored under nitrogen atmosphere and cooling on. The OSI was determined by accelerated Rancimat test, it was used for 3.0 ± 0.1 g of sample temperature parameters (110, 130 and 150 °C) and air flow (15, 20 and 25 L/h). Applying the Rancimat test, it was found by ANOVA (p < 0.05) that the influence of temperature on the OSI was highly significant, whereas the only air flow was significant. By extrapolation method, values were calculated at usual temperatures OSI oil storage (25 °C) to give stability times 214, 242 and 222 days, also the activation energy of the oxidation reaction of sesame oil for different air flows, is 97.28, 98.79 and 96.86 kJ / mol for 15, 20 and 25 L/h respectively.